Analysis Of Forward Storage Platform In 50 Pax Crane Barge With An Finite Element Method - Meida Perwira Antartika; Budianto Budianto; Muhamad Ari (Jurnal Teknologi dan Riset Terapan (JATRA), 2020)
Hull construction must comply with the rules or classifications that have been recognized in the world of international shipping, in designing a storage platform designed by PT. X is designed for partners based reference, as a rule forms the design and calculations no rules. As for the mechanical properties of the material provisions remain in rules. Rules are used for shipbuilding 50 P.A.X crane barge is that BV (Bureau Veritas) rules. The analysis in this study using the finite element method-based software. With the software will be able to look forward strength and simulation constructs storage platforms that will support the weight of 6,4 tons (3,2 tons on portside and 3,2 tons on start board) in a static condition, dynamic, and impact. It aims to anticipate the possibility of the construction design error forward storage platform that could lead to an accident on the ship. Construction material storage platform forward using BV grade A steel.